Comparison of self-measured diurnal intraocular pressure profiles using rebound tonometry between primary angle closure glaucoma and primary open angle glaucoma patients - Shaoying Tan (2018)
© 2017 Tan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Purpose To document the diurnal intraocular pressure (IOP) profile with rebound tonometry performed by primary glaucoma patients in non-clinic environment. Patients and methods Fifty-three medically-treated eyes of 31 primary angle closure glaucoma (PACG) and 22 primary open angle glaucoma (POAG) patients with no previous eye surgery were recruited. Diurnal IOP was measured 5 times per day at four-hourly intervals from 08:00 to 24:00 for 1 week in patients' study eye using rebound tonometry in a non-clinic environment. The diurnal IOP profiles were compared between PACG and POAG eyes. Results For both PACG and POAG eyes, mean patient-measured IOP was highest in the morning, gradually decreased over the course of a day, and was lowest by midnight (p < 0.001). The diurnal IOP fluctuation ± 1 standard deviation (SD), as documented by SD in daily IOP values, was lower in PACG group (1.6 ± 1.1 mmHg) than in POAG group (2.0 ± 1.2 mmHg; p = 0.049). The mean trough IOP ± 1 SD was higher in PACG group (12.9 ± 2.8 mmHg), compared to POAG group (11.5 ± 3.8 mmHg; p = 0.041). The mean IOP level at midnight ± 1 SD in PACG group (14.0 ± 3.2 mmHg) was higher than that in POAG group (12.1 ± 3.7 mmHg; p = 0.013). Conclusions IOP in primary glaucoma patients was highest in the morning, and decreased over the course of a day in non-clinic environment. Treated diurnal IOP fluctuation seemed to be greater in POAG than PACG eyes.